Understanding the holobiont: the interdependence of plants and their microbiome - Sánchez-Cañizares, C; Jorrin, B; Poole, P; Tkacz, A (Elsevier, 2017)
The holobiont is composed by the plant and its microbiome. In a similar way to ecological systems of higher organisms, the holobiont shows interdependent and complex dynamics [1,2]. While plants originate from seeds, the microbiome has a multitude of sources. The assemblage of these communities depends on the interaction between the emerging seedling and its surrounding environment, with soil being the main source. These microbial communities are controlled by the plant through different strategies, such as the specific profile of root exudates and its immune system. Despite this control, the microbiome is still able to adapt and thrive. The molecular knowledge behind these interactions and microbial “-omic” technologies are developing to the point of enabling holobiont engineering. For a long time microorganisms were in the background of plant biology but new multidisciplinary approaches have led to an appreciation of the importance of the holobiont, where plants and microbes are interdependent.